Pengalaman dan Pemaknaan Remaja Terhadap Pembelajaran Seksualitas Berbasis Komunitas dalam Program Edukasi Balai Penyuluhan Keluarga Berencana - Rivo Nugroho; Desika Putri Mardiani; Fitria Ayu Rahmadika; Tri Ulya Qodriyati (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2026)
Sexuality education constitutes an important aspect in supporting adolescent development; however, its implementation within community contexts is often influenced by strong social and cultural norms. This condition causes adolescents’ learning experiences to remain insufficiently understood, particularly from their subjective perspectives. This study aims to explore adolescents’ experiences and meaning-making regarding community-based sexuality education. The study employed a qualitative approach with a phenomenological design. The research was conducted within a youth organization in Wedi Village, Gedangan District, involving 15 informants consisting of 10 adolescents as primary informants and 5 supporting informants, including the neighborhood head, youth organization administrators, and community leaders. Data were collected through semi-structured in-depth interviews, observation, and documentation. Data analysis was conducted using thematic analysis based on Braun and Clarke’s framework, supported by triangulation and member checking to ensure data validity. The findings reveal that adolescents tend to interpret sexuality in normative ways, experience conflicts between social values and personal curiosity, and engage in community learning spaces that are not yet fully open and inclusive. These findings indicate that community-based sexuality education is not merely a process of information delivery, but also a social experience shaped by norms, interactions, and adolescents’ subjective meaning-making processes. This study contributes to emphasizing the importance of developing sexuality education approaches that are more dialogical, participatory, and contextual within community environments.